Issues in Teaching and Learning of Education for Sustainability: Theory into Practice, 1st edition - Chang, Chew-Hung (Routledge, 2020)
In a fast-changing, globalising world, the teaching and implementation of a curriculum for Education for Sustainability (EfS) has been a challenge for many teachers. Issues in Teaching and Learning of Education for Sustainability highlights the issues and challenges educators and academics face in implementing EfS and gives examples of what an EfS curriculum may look like and how some institutions translate the theory into practice.